All-round performance improvement of semitransparent perovskite solar cells by a pressure-assisted method. Issue 42 (13th October 2021) - Yu, Yuan; Shang, Meijia; Wang, Tao; Zhou, Qian; Hao, Yuying; Pang, Zhiyong; Cui, Deliang; Lian, Gang; Zhang, Xijian; Han, Shenghao
Abstract : A pressure-assisted method was used to achieve a remarkable enhancement in the crystallinity and flatness of ultra-thin MAPbI3 films. This process facilitates an all-round improvement in the photoelectric and optical properties of solar cells. Abstract : Recently, the demand for semi-transparent perovskite solar cells (SPSCs) to serve as semitransparent windows for urban building and automobile applications has grown. However, it is challenging to prepare high-quality ultra-thin perovskite films, significantly restricting the development of SPSCs. In this paper, we report an all-round performance improvement of ultra-thin perovskite films and SPSCs prepared by using a thermal-pressed recrystallizing (TPR) method. The average grain size of perovskite films increased from ∼340 nm to ∼1.64 μm, after the TPR treatment, along with a dramatic decrease in the surface root mean square (RMS) roughness from ∼14.9 nm to ∼1.04 nm. The SPSCs fabricated by the TPR method showed a significant improvement in all-round performance, such as open-circuit voltage, short-circuit current, fill factor, power conversion efficiency, transmittance and stability. The average power conversion efficiency showed a significant increase of up to 32.8% after TPR treatment, indicating the potential for the development of high performance semitransparent photovoltaic windows.